Analisis Pengaruh Konflik Pekerjaan-Keluarga (work-family conflict) Dan Stres Terhadap Kepuasan Kerja Pada Karyawan Wanita Di Sekretariat Daerah (Setda) Kabupaten Di Pulau Lombok - Qaedi Taris Ardita; Agusdin Agusdin; Lalu Muhammad Furkan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2018)
This study aims to (1) analyze the effect of  Work-family conflict on job satisfaction; (2) analyze the effect of Work-Family Conflict on work stress ; (3) analyze the effect of work stress on job satisfaction (4) analyze the effect of work-family conflict on job satisfaction mediated by work stress. Type of research is quantitative with causal assosiative. The population in this study was on Female Employees at the District Secretariat on Lombok Island. The number of members of the population is 188 people.   Determination of the sample by purposive sampling method. Sample criteria are employees who are married. The number of samples is 92 people. Data collection techniques or tools use a questionnaire. The analysis tool uses PLS (Partial Least Square) with SmartPLS 3.0 program. The results showed that (1) the Conflict of Family Work had a negative effect not significant on job satisfaction; (2) Work-Family Conflict have a positive significant effect on work stress; (3) Job stress has a negative significant effect on job satisfaction; (4) Work- Family Conflict negatively affects on job satisfaction mediated by work stress.work-family conflict, job stress,  job satisfaction, female employees, Lombok island.